High prevalence and species diversity of Helicobacter spp. detected in wild house mice - Wasimuddin; Čížková, Dagmar; Bryja, Josef; Albrechtová, Jana; Hauffe, Heidi C; Piálek, Jaroslav (Applied and environmental microbiology, 2012)
PCR diagnostics detected 100% prevalence of Helicobacter in 425 wild house mice (Mus musculus) from across central Europe. Of seven species identified, the five most frequent were Helicobacter rodentium (78%), H. typhlonius (53%), H. hepaticus (41%), H. bilis (30%), and H. muridarum (1%). Double infections were more common (42%) than single (30%) and triple (21%) infections. Wild house mice could be considered potential reservoirs of Helicobacter strains for both humans and other vertebrates.
Keywords: Animals; Helicobacter; ribozomální DNA; DNA, Ribosomal; Prevalence; DNA bakterií; Coinfection; RNA, Ribosomal, 16S; DNA, Bacterial; divoká zvířata; shluková analýza; Molecular Sequence Data; Mice; myši; koinfekce; Phylogeny; prevalence; molekulární sekvence - údaje; Animals, Wild; Sequence Analysis, DNA; zvířata; sekvenční analýza DNA; Helicobacter Infections; Cluster Analysis; fylogeneze; RNA ribozomální 16S; infekce vyvolané Helicobacter pylori